Тенденції в динаміці рослинництва України: ефекти згладжування рядів даних - Дмитрієва, Вікторія Анатоліївна; Dmytriieva, Viktoriia (Дніпровський державний аграрно-економічний університет, 2018)
Аграрна індустрія є джерелом постачання населення продуктами харчування та забезпечує підприємства країни сировиною. Ця сфера суттєво впливає на розвиток економіки в цілому, оскільки належить до категорії галузей, які формують валову додану вартість і роблять свій внесок у валовий внутрішній продукт України. Окрім цього, сільськогосподарський сектор є одним з експортерів, прибутки від діяльності якого обумовлюють формування позитивного або негативного торговельного сальдо. З огляду на сучасне становище національного господарства країни завжди актуально утримувати в полі зору релевантні дані щодо ситуації в галузі та вчасно виконувати їх аналіз, що дозволятиме відстежувати протилежні тенденції в динаміці та виявляти фактори, які спричиняють зміни в їх напрямках. Певною мірою аграрна галузь відповідає за продовольчу безпеку всієї країни, оскільки має забезпечувати все населення продуктами харчування належної якості. Водночас, ця галузь має свої особливості, які не властиві іншим секторам економіки, наприклад, сезонність, залежність від природно-кліматичних умов та пори року, тривалість біологічного часу росту тварин і рослин тощо. З метою вивчення аналізу тенденцій і кореляції динамічних рядів даних автором було застосовано метод Ходріка-Прескотта для очищення даних від випадкових коливань, створено скрипт в середовищі Octave, що дозволило реконструювати довготермінові тенденції в сфері рослинництва та відобразити результати аналізу графічно. Аналіз проведено за період 1990-2017 рр. за даними Державної служби статистики України. Agriculture provides with vitally-necessary products to the country population and forms tendency of the economy development. Agrarian sector is one of the main components of the economy, which creates gross value added, and therefore forms the gross domestic product of the country. This branch is one of the big suppliers of raw materials and food products for export. It causes the positive or negative trade balance. It is always relevantly to monitor state and development of agriculture, which allows tracking straight or opposite trends in the dynamics, identify causes of the directions’ changes. In addition, the agrarian sector provides food to the population, and therefore it is responsible for food security throughout the country. Simultaneously, agricultural branch has peculiarities, which unavailable in industrial production or some kinds of service. Such specific points include seasonality, term of biologic growth of crops and animals, nature and climate conditions and others. Besides that, it is important to take into consideration economical fluctuations like inflation of national or foreign currencies, prices increasing, economy decline, strength and weakness of competitors etc. Comparison of different factors shows that nature and climate have the such effect on productivity of agriculture in Ukraine as economical changes. What the tendencies will describe dynamic of the branch if unexpected couses will be excluded? What the form of curve-trend can present cleaned dynamic in crop production? How many directions of it will be formed by factors? To answer the questions author worked out data sets, which have been got from the official site of State Statistics Service of Ukraine. They include indicators of square under crops and harvest of beetroot, potatoes, sunflower, vegetables, crops. Investigated period covers term from 1990 to 2017 years. Author applied HP-method (from Hodric R. J. and Prescott E. C.) in order to clean data from random fluctuations and developed script in computer aided mathematical system GNU Octave in order to investigate long-term dynamics in crop production, its correlations and interdependences of the indicators. In addition, a graph-method analysis has been performed here.
Tendencies in Ukrainian dynamics of crop production: effects of data sets smoothing
Keywords: динаміка; dynamics; довготермінова тенденція; long-term tendency; розвиток; development; посівна площа; crop area; продуктивність; productivity; урожайність; harvest